The role of defining the sentinel lymph node in the treatment of low-risk highly differentiated thyroid cancer (review of literature) - M. E. Boriskova; U. V. Farafonova; P. A. Pankova; M. A. Bykov; E. A. Ramazanova; N. S. Feshenko; A. A. Zakharenko; N. A. Yaitsky (Вестник хирургии имени И.И. Грекова)
The definition of a sentinel lymph node is a technique that appeared at the middle of the 20th century. For a number of malignant neoplasms, the definition of a sentinel lymph node is standard procedure, but for highly differentiated thyroid cancer, the data is conflicting. The role of prophylactic central compartment lymph node dissection in the clinical N0 stage is not established. Sentinel lymph node detection seems to be the possible way to reduce the risk of persistence and recurrence of highly differentiated thyroid cancer.